Finance and Development, September 2015. (Finance and Development; Finance and Development, 2015)
This chapter presents the point of view and ideas of Sabina Alkire, an economist. Alkire wants the Multidimensional Poverty Index to be part of a data revolution to guide the fight against poverty. According to Alkire, learning to meditate soothed away what she describes as the temper tantrums of her childhood. The chapter also highlights the fact that an index is only as good as its underlying data, and in emerging market economies that quality is often inadequate. The quest for better poverty metrics coincides with growing doubts about the ability of conventional statistics, especially GDP, to gauge economic growth in the digital economy, let alone well-being, welfare, and environmental sustainability.